Prediction of the Geometric Renewal Process - Kanišauskas, Vaidotas; Piaseckienė, Karolina (Lithuanian Journal of Statistics, 2017)
The first part of the paper presents major concepts and theoretical statements on prediction of processes. The second part presents the obtained results on the geometric renewal process by indicating its distribution which has a binomial distribution and is a process with independent and stationary increments. Further, having applied the theory introduced in the first part to the geometric renewal process, the sufficient and unbiased prediction with the minimum-variance has been found.
Keywords: renewal process; binomial distribution; prediction; unbiased prediction